1958
DOI: 10.1111/j.1570-7458.1958.tb00033.x
|View full text |Cite
|
Sign up to set email alerts
|

MULTIPLICATION OF POTATO LEAF ROLL VIRUS IN THE APHID MYZUS PERSICAE (SULZ.)

Abstract: Insect‐to‐insect transmission of potato leaf roll virus proved possible by injecting either juice or haemolymph from viruliferous Myzus persicae into virus‐free ones. In serial transmission experiments, in which injection of haemolymph was practised, the virus could be carried through as many as 15 successive aphid‐to‐aphid passages without access of inoculated insects to any plants that are susceptible to leaf roll. The theoretical dilution of original virus used for the inoculation in the 15th passage would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

1963
1963
2001
2001

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(10 citation statements)
references
References 16 publications
0
8
0
2
Order By: Relevance
“…1928) and later applied to aphids by Rochow (1960), or by injecting them with the suspension, as first for leafhoppers by Storey (1932) and Black and Brakke (1952) and later for aphids by Stegwee and Ponsen (1958). In fact, the technique of membrane feeding was first developed by Storey (1932) for demonstrating the filterability of maize streak virus which is not mechanically transmissible from plant to plant.…”
Section: Fig 4 Herinbreng In Toetsplanten Van Niet-rnet-sap-over-tementioning
confidence: 99%
“…1928) and later applied to aphids by Rochow (1960), or by injecting them with the suspension, as first for leafhoppers by Storey (1932) and Black and Brakke (1952) and later for aphids by Stegwee and Ponsen (1958). In fact, the technique of membrane feeding was first developed by Storey (1932) for demonstrating the filterability of maize streak virus which is not mechanically transmissible from plant to plant.…”
Section: Fig 4 Herinbreng In Toetsplanten Van Niet-rnet-sap-over-tementioning
confidence: 99%
“…The experiments were carried out with the isolate of PLRV used by Stegwee and Ponsen (1958). The virus was maintained in P.floridana by repeated aphid transfers.…”
Section: Methodsmentioning
confidence: 99%
“…) (Stegwee and Ponsen, 1958), affects the development of this aphid. Janssen (1929) and Arenz (1951) reported a more rapid increase in number of M. persicae on leafroll-diseased potato plants than on healthy ones.…”
Section: Introductionmentioning
confidence: 95%
“…Since PLRV multiplies in its vector (Stegwee and Ponsen, 1958) this increase during the larval stage of M. persicae must be due to virus multiplication in the aphid. In the imaginal stage of the aphid no virus multiplication probably takes place, although the virus could be recovered from the haemolymph (Stegwee and Ponsen, 1958). According to Harrewijn and Noordink (in prep.…”
Section: Fig 2 the Ability Ofmentioning
confidence: 99%
“…Moreover, Day (1955) found that the percentage of PLRV-diseased test plants increased with the time the aphids had stayed on the immune host Brassica chinensis. On the other hand, Stegwee and Ponsen (1958) demonstrated big variations in the infection ability of viruliferous aphids during their life.…”
Section: Introductionmentioning
confidence: 99%